William Lyon Mackenzie King: The Corporate Man - Ropel-Morski, Hermina P. (My University, 1978)
This study consists of an examination of the political philosophy of William Lyon Mackenzie King. An examination of King's book Industry and Humanity reveals his political philosophy, as expressed in his book, to be that of corporatism. Although a professed liberal and leader of the Liberal Party in Canada for many years, King's advocation of corporatism as a means of overcoming industrial and social conflicts, is seen as a conservative measure.
King's success as a labour conciliator in industrial disputes during the early years of this century and later political success earned him the name of "conciliator". However in this study it is argued that King was in fact a "controller" of events. Data provided by the King diaries and other material in the literature has been utilized within the framework of Object-Relations theory. Within this framework inferences have been drawn to show that King was in fact a "controller" and not a "conciliator" due in part to an obsessive-compulsive personality.
Keywords: Political Science; Political Science